Nothing sacred : Nazi espionage against the Vatican ; 1939 - 1945 - Alvarez, David J. (Studies in intelligence, 1997)
Nothing Sacred is the first book to document the Nazi espionage campaign against the Vatican in the Second World War. Nazi Germany considered the Catholic Church to be a serious threat to its domestic security and its international ambitions. In Germany, Hitler's agents recruited informants to provide intelligence on Church finances, and on the political views and activities of bishops, priests and lay Catholics. In Rome, however, German attempts to penetrate the Papacy were less successful, with the efforts of the local Gestapo office proving largely futile. The German codebreaking operation on the other hand was more successful: the Nazis systematically intercepted, decoded and read secret communications between the Pope and his representatives worldwide. Written by two leading authorities on Vatican history, this work will prove fascinating reading for those interested in Second World War history, intelligence studies and the history of the Catholic Church.